Colon cleansing efficacy and safety with 1 L NER1006 versus sodium picosulfate with magnesium citrate: a randomized phase 3 trial - Schreiber, Stefan; Baumgart, Daniel C.; Drenth, Joost P. H.; Filip, Rafał S.; Clayton, Lucy B.; Hylands, Kerry; Repici, Alessandro; Hassan, Cesare; on behalf of the DAYB Study Group (Endoscopy, 2019)
Background Polyethylene glycol (PEG) bowel preparations are widely used for precolonoscopy bowel cleansing. This phase 3 trial assessed the efficacy, safety, and tolerability of the novel 1 L PEG-based NER1006 vs. sodium picosulfate plus magnesium citrate (SP + MC) in day-before dosing.Methods Patients requiring colonoscopy were randomized (1 : 1) to receive NER1006 or SP + MC. Cleansing was assessed on the Harefield Cleansing Scale (HCS) and Boston Bowel Preparation Scale (BBPS) using central readers. Two primary end points were assessed: overall colon cleansing success and high-quality cleansing of the right colon. Intention-to-treat (modified full analysis set [mFAS]) and per protocol (PP) analyses were performed. Results Of 515 patients, efficacy was analyzed in 501 (NER1006, n = 250; SP + MC, n = 251) and 379 patients (NER1006, n = 172; SP + MC, n = 207) in the mFAS and PP analyses, respectively. Non-inferiority of NER1006 vs. SP + MC was established in the mFAS for both overall cleansing (62.0 % vs. 53.8 %; P = 0.04) and high-quality cleansing in the right colon (4.4 % vs. 1.2 %; P = 0.03). Superiority of NER1006 was demonstrated using HCS in the PP set for overall cleansing success (68.0 % vs. 57.5 %; P = 0.02) and right colon high-quality cleansing (5.2 % vs. 1.0 %; P = 0.02) and using BBPS in the mFAS for overall cleansing success (58.4 % vs. 45.8 %; P = 0.003) and right colon high-quality cleansing (4.0 % vs. 0.8 %; P = 0.02). Mean segmental scores for 4/5 segments were higher with NER1006 (P ≤ 0.04). Both treatments were well tolerated, with more mild adverse events for NER1006 (17.0 % vs. 10.0 %; P = 0.03).Conclusions Colon cleansing with NER1006 vs. SP + MC was non-inferior (mFAS) and superior (PP), with acceptable safety.European Clinical Trials Database (EudraCT)2014-002186-30TRIAL REGISTRATION: Multicenter, randomized, parallel group, phase 3 study 2014-002186-30 at https://eudract.ema.europa.eu/